2009
DOI: 10.1080/14767050902994614
|View full text |Cite
|
Sign up to set email alerts
|

Impact of intrapartum factors on oxidative stress in newborns

Abstract: The oxidative status of the newborn is not simply a reflection of the mode of delivery and type of anesthesia. The impact of gestational age and birth weight appears to be crucial. This must be considered when planning elective delivery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
9
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 26 publications
0
9
0
Order By: Relevance
“…Birth weight and gestational age could be important. 49 Surgery-related parameters such as the urgency of delivery, the duration of surgery, and the interval from uterine incision to delivery, are known to influence neonatal outcomes. 50 Maternal inhaled oxygen concentration, minute ventilation, intravenous fluid volume, blood pressure, vasopressor administration and extent of sympathetic block may be more important than the nature of the anesthetic agents.…”
Section: Discussionmentioning
confidence: 99%
“…Birth weight and gestational age could be important. 49 Surgery-related parameters such as the urgency of delivery, the duration of surgery, and the interval from uterine incision to delivery, are known to influence neonatal outcomes. 50 Maternal inhaled oxygen concentration, minute ventilation, intravenous fluid volume, blood pressure, vasopressor administration and extent of sympathetic block may be more important than the nature of the anesthetic agents.…”
Section: Discussionmentioning
confidence: 99%
“…4a-OHC is known to be formed by cholesterol autoxidation [9][13] during oxidative stress, but it is not known if it can be formed enzymatically as well. There are inconsistencies in the literature on the oxidative effect on mother and child by uncomplicated vaginal delivery or CS [34][35][36][37][38][39][40][ [39][40][41][42][43][44][45], possibly due to the use of different markers.…”
Section: Discussionmentioning
confidence: 99%
“…Correlation analysis revealed that blood level of MDA of both mother and cord blood correlated negatively with birth weight of the neonates. Malondialdehyde levels in fetal serum have previously also been shown to correlate negatively with fetal weight [24]. Total antioxidant capacity of blood in both mother and fetus correlated positively with fetal weight, indicating significant impact of antioxidant potential on fetal birth weight, and thus, the incidence of FGR.…”
Section: Discussionmentioning
confidence: 89%